A Non-Dicer RNase III and Four Other Novel Factors Required for RNAi-Mediated Transposon Suppression in the Human Pathogenic Yeast Cryptococcus neoformans. Issue 7 (1st July 2019) - Burke, Jordan E; Longhurst, Adam D; Natarajan, Prashanthi; Rao, Beiduo; Liu, John; Sales-Lee, Jade; Mortensen, Yasaman; Moresco, James J; Diedrich, Jolene K; Yates, John R; Madhani, Hiten D
Abstract: The human pathogenic yeast Cryptococcus neoformans silences transposable elements using endo-siRNAs and an Argonaute, Ago1. Endo-siRNAs production requires the RNA-dependent RNA polymerase, Rdp1, and two partially redundant Dicer enzymes, Dcr1 and Dcr2, but is independent of histone H3 lysine 9 methylation. We describe here an insertional mutagenesis screen for factors required to suppress the mobilization of the C. neoformans HARBINGER family DNA transposon HAR1 . Validation experiments uncovered five novel genes ( RDE1-5 ) required for HAR1 suppression and global production of suppressive endo-siRNAs. The RDE genes do not impact transcript levels, suggesting the endo-siRNAs do not act by impacting target transcript synthesis or turnover. RDE3 encodes a non-Dicer RNase III related to S. cerevisiae Rnt1, RDE4 encodes a predicted terminal nucleotidyltransferase, while RDE5 has no strongly predicted encoded domains. Affinity purification-mass spectrometry studies suggest that Rde3 and Rde5 are physically associated. RDE1 encodes a G-patch protein homologous to the S. cerevisiae Sqs1 /Pfa1, a nucleolar protein that directly activates the essential helicase Prp43 during rRNA biogenesis. Rde1 copurifies Rde2, another novel protein obtained in the screen, as well as Ago1, a homolog of Prp43, and numerous predicted nucleolar proteins. We also describe the isolation of conditional alleles of PRP43, which are defective in RNAi. This work reveals unanticipated requirements for a non-Dicer RNase III and presumptive nucleolar factors for endo-siRNA biogenesis and transposon mobilization suppression in C. neoformans .